Bewertungsinteraktionen in der Theaterpause Eine gesprächsanalytische Untersuchung von Pausengesprächen im Theaterfoyer - Hrncal, Christine (Empirische Linguistik / Empirical Linguistics, 2020)
This study inquires into the specific forms of critical interaction that occur in conversations during intermissions in the theater lobby. Using conversational analysis, it reconstructs how the assessments shared during these interactions impact audience members' attitudes to the content of the theater piece. The book adds to our understanding of the little-studied area of non-professional private communication about performative art.